Social constructionism and the effects of media's portrayal of Nigeria's economic recession on foreign direct investment : Društveni konstrukcionizam i učinci medijskog prikaza nigerijske gospodarske recesije na strane izravne investicije - Ehondor, Beryl Annette (Array, 2021)
Although Nigeria has the largest economy in Africa, it has been bedeviled by various issues in recent times, which has led to its experience of an economic recession. Its over-dependence on foreign products, the activities of militants and pipeline vandals in the Niger-Delta, poor economic planning and the delayed budget signing are some of the issues that have being credited to the fall into recession. However, some economists have suggested that Nigeria"s economy has the potential to rise from the recession and have identified the inflow of foreign direct investments as one of the key factors that will contribute to the rise. On the other hand, the media"s reporting of Nigeria"s recession seems to have caused mixed reactions from among the public who worry about their daily bread. Potential investors, both local and foreign, are also not left out in the expression of uncertainty. Since they rely on the media to provide information on the situation of the Nigerian economy, the power of the media in the making or marring of the government"s encouragement of FDI to boost the economy cannot be underestimated. The power of the media, which appears to be able to determine or construct the position and perception of individuals/organisation follow it can be relat-ed to the theory of social constructionism. So-cial constructionism suggests that the media"s have the capacity to selectively reproduce and construct the reality of any situation – in this case, Nigeria"s recession. However, it also acknowledges that the meanings offered by the media can be negotiated or rejected by those to whom it is directed. This study explores the capacity of the media"s construction of Nigeria"s economic recession to influence the inflow of foreign direct investments.